The Forest Conservation Model According to Buddhist Ethics of Loei Provincial Sangha - Boontawong, Boonyawat; Thongpan, Suwin; Leeka, Jaras (Dhammathas Academic Journal, 2023)
The objectives of this research were: 1) to study the forest situation and forest conservation of temples in Loei Province; 2) to study Buddhist ethics in forest conservation; 3) to create a model of forest conservation according to Buddhist ethics of Loei Provincial Sangha. This study was carried out by means of qualitative research through studying information from the Tipitaka, academic papers, and related research. There were 38 key informants. The obtained data were interpreted by descriptive analysis based on an inductive method. The research results were as follows: 1. The situation of forests and forest conservation of temples in Loei Province: forests in Loei Province began to disappear due to five main reasons: (1) population increase, (2) urban expansion, (3) use of modern technology, (4) construction of various buildings and (5) the need for areas for agriculture and livestock. Therefore, it is necessary to plant forests and take care of and maintain forests. 2. Buddhist ethics in forest conservation: Buddhist ethics is the principle of behavior that humans should treat human beings and the environment. The principles of Buddhist ethics used in forest conservation to achieve fertility are the Four Sammappadhāna and Four Sappāya. 3. The model of forest conservation according to Buddhist ethics of the Sangha of Loei Province: there was a model that applied two Buddhist ethics principles: the Four Sammappadhāna and Four Sappāya to create three models of forest conservation of the Loei Provincial Sangha: afforestation, forest care, and forest maintenance leading to stability and sustainability.